Microliteracy and the Discourse of Canadian Multiculturalism - Reid, Cameron; Nash, Rachel (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2004)
AbstractThis article outlines the chaotic proliferation of multicultural micro-literacies over the decades since the Canadian government first brought the concept of multiculturalism to the national stage in the mid-1960s. The authors define multicultural literacy in terms of patterned and sustained orientations to multiculturalism discourse — orientations that manifest themselves by way of recurrent social and textual practices. In the years prior to 1988 and the official enactment of multiculturalism in Canada, the discourse lent itself to naïve and largely optimistic renderings in a phase of literacy development described in the essay as protoliteracy. Subsequent efforts by the Canadian government to mute the discourse, even as it made multiculturalism into official policy, cleared the way for a post-literate multiplication of multicultural literacies in this country, which severely fragmented and undermined the discourse in the process.